Analisis Rasio Keuangan Dalam Mengukur Kinerja Keuangan Pada Perusahaan Manufaktur Terdaftar Pada Bursa Efek Indonesia: Studi kasus PT. Pabrik Kertas Tjiwi Kimia Tbk Tahun 2021-2023 - Tisa Aprillia; Yulis Juncy Apriada; Sindi Lorenza (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Tjiwi Kimia Tbk Paper Factory, the world's leading producer of pulp, paper and paper products, has an important role in the national economy. Financial ratio analysis highlights a company's financial health, focusing on liquidity, solvency, activity, and profitability. The aim of this research is to understand and assess the company's financial health and measure overall financial performance. From this research, it can be seen that ratio analysis shows liquidity fluctuations, a significant decrease in profitability, and a lack of efficient use of assets. Although the company's solvency remains maintained, the main challenge lies in operational efficiency and profit growth in proportion to the increase in assets. In conclusion, a more effective strategy is needed in debt management, increasing operational efficiency, and optimizing asset use to improve overall company performance